Discovery of aphid-transmitted Rice tiller inhibition virus from native plants through metagenomic sequencing. - Wenkai Yan; Yu Zhu; Wencheng Liu; Chengwu Zou; Bei Jia; Zhong-Qi Chen; Yanhong Han; Jianguo Wu; Dong-Lei Yang; Zhongkai Zhang; Lianhui Xie; Baoshan Chen; et al. (PLoS Pathogens, 2023)
A major threat to rice production is the disease epidemics caused by insect-borne viruses that emerge and re-emerge with undefined origins. It is well known that some human viruses have zoonotic origins from wild animals. However, it remains unknown whether native plants host uncharacterized endemic viruses with spillover potential to rice (Oryza sativa) as emerging pathogens. Here, we discovered rice tiller inhibition virus (RTIV), a novel RNA virus species, from colonies of Asian wild rice (O. rufipogon) in a genetic reserve by metagenomic sequencing. We identified the specific aphid vector that is able to transmit RTIV and found that RTIV would cause low-tillering disease in rice cultivar after transmission. We further demonstrated that an infectious molecular clone of RTIV initiated systemic infection and causes low-tillering disease in an elite rice variety after Agrobacterium-mediated inoculation or stable plant transformation, and RTIV can also be transmitted from transgenic rice plant through its aphid vector to cause disease. Finally, global transcriptome analysis indicated that RTIV may disturb defense and tillering pathway to cause low tillering disease in rice cultivar. Thus, our results show that new rice viral pathogens can emerge from native habitats, and RTIV, a rare aphid-transmitted rice viral pathogen from native wild rice, can threaten the production of rice cultivar after spillover.